Chronological association between alopecia areata and autoimmune thyroid diseases: A systematic review and meta‐analysis. Issue 8 (14th June 2019) - Kinoshita‐Ise, Misaki; Martinez‐Cabriales, Sylvia Aide; Alhusayen, Raed
Abstract: The association between alopecia areata (AA) and autoimmune thyroid diseases (AITD) has been suggested; however, the chronological relationship between AA and AITD remains elusive. A systematic review and meta‐analysis were conducted to assess the association between AA and AITD focusing on the prevalence of thyroid antibodies, thyroid diseases and serological thyroid dysfunctions, respectively. Data collection was performed in October 2018 by searching for articles in two electronic databases: Medline and Embase. Case–control, cohort and cross‐sectional studies were included. Meta‐analysis of studies eligible for quantitative synthesis was performed to estimate pooled odds ratios of thyroid antibodies; thyroid peroxidase antibody (TPO‐Ab) and thyroglobulin antibody (TG‐Ab), diagnosed thyroid diseases and serological thyroid dysfunctions. Four hundred and eighty nine research papers were identified and 17 studies with 262 581 patients and 1 302 655 control subjects were included for quantitative synthesis. AA was significantly associated with both TPO‐Ab and TG‐Ab. In comparison, there was no significant association between AA and diagnosed hypothyroidism or hyperthyroidism and serological hypothyroidism or hyperthyroidism. In conclusion, AA is significantly associated with the existence of thyroid antibodies rather than with clinical or laboratory thyroid abnormality. Lack of long‐term follow‐up data is a limitation of the existing published work. Our findings do not support routine screening of thyroid diseases for asymptomatic AA patients but highlight the potential future risk of AITD particularly in severe and refractory AA.